Performance evaluation of protein recovery from Argentinian soybean extruded-expelled meals under different operating conditions - Accoroni, Cecilia; Godoy, Ezequiel; Reinheimer, María Agustina (Elsevier, 2019)
The soybean extruded-expelled (EE) meals are the byproduct of the process commonly used by small or medium-sized Argentinian companies for obtaining soy oil. In this work, the performance of the pH-shifting process for obtaining a protein product from the EE meals was evaluated as a strategy for on-site value-adding. The EE meals were subjected to the proposed pH-shifting process under different operating parameters at the alkaline extraction stage (2 and 3 cycles at 55, 60 and 65 °C with and without sodium sulfite) and isoelectric precipitation stage (0 °C and 20 °C with hydrochloric and phosphoric acids), which constitute the controlling steps in an industrial scaling of the process. The pH-shifting process consisting of 3 alkaline extraction cycles at 60 °C followed by isoelectric precipitation at low temperature using hydrochloric acid was found to be well suited for obtaining a final product with a protein content upwards of 75%.